1994
DOI: 10.1677/jme.0.0130303
|View full text |Cite
|
Sign up to set email alerts
|

Induction of c-fos in pituitary cells by thyrotrophin-releasing hormone and phorbol 12-myristate 13-acetate depends upon Ca2+ influx

Abstract: The role of cytosolic free Ca2+ ([Ca2+]i) in the induction of the immediate early gene c-fos by TRH or by phorbol 12-myristate 13-acetate (PMA) was studied in the clonal pituitary cell line GH4C1. It was found that c-fos mRNA levels were rapidly and transiently increased by TRH at physiological concentrations (1-100 nM). The effect of TRH was dependent on a rise in [Ca2+]i, and TRH stimulation of Ca2+ influx was essential for c-fos induction. Cell depolarization with K+, which produces a [Ca2+]i rise by solici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…Our previous work has also demonstrated that removal of calcium from the cell culture medium results in the reduction of BCP crystal-induced c-fos mRNA expression, indicating that an influx of extracellular calcium is required for maximal c-fos induction (18). These results are similar to the work of others showing PKC and extracellular calcium requirements for c-fos induction (48,49).…”
Section: Discussionsupporting
confidence: 86%
“…Our previous work has also demonstrated that removal of calcium from the cell culture medium results in the reduction of BCP crystal-induced c-fos mRNA expression, indicating that an influx of extracellular calcium is required for maximal c-fos induction (18). These results are similar to the work of others showing PKC and extracellular calcium requirements for c-fos induction (48,49).…”
Section: Discussionsupporting
confidence: 86%
“…GH4C1 cells stimulated by TRH in medium with low free extracellular Ca 2ϩ result in the suppression of sustained intracellular Ca 2ϩ signals. (32,36). We demonstrated marked differences in MKP-1 gene expression in the absence or presence of extracellular Ca 2ϩ after TRH stimulation, which defines a physiological role for calcium in MKP-1 induction associated with the release of the block to elongation.…”
Section: -41mentioning
confidence: 72%
“…Previous reports have shown that the prolonged phase of [Ca 2ϩ ] i spiking was essential to enhance and maintain proto-oncogene mRNA levels over time (31,32,36 A, the rat MKP-1 gene was amplified by PCR, cloned, and sequenced (GenBank TM accession number AF357203), as described under "Experimental Procedures." The cloned fragment of 2.9 kilobase pairs was used to prepare random labeled DNA probes (probes 1-5) for Southern analysis.…”
Section: Induction Of Mkp-1 Mrna By Trh Depends Upon Ca 2ϩmentioning
confidence: 99%
“…Ϫ fibroblasts to agents that elevate intracellular levels of calcium and/or cAMP, since these pathways were shown to synergize in c-fos activation (46,47). In Ltk Ϫ cells, PMA, IBMX ϩ 8-Br-cAMP, or calcium ionophore (A23187) generated only a minor induction of c-fos mRNA (Fig.…”
Section: C-fos Induction In Ltk ϫ Cells Requires the Concerted Actionmentioning
confidence: 98%